Digital Engineering Measures: Research and Guidance. Issue 1 (12th April 2022) - McDermott, Tom; Henderson, Kaitlin; Salado, Alejandro; Bradley, Joseph
ABSTRACT: Digital Engineering and Model‐Based Engineering continue to grow in adoption across the systems engineering community. However, programs and enterprises still struggle to quantify the value of this digital transformation. Research conducted by the Systems Engineering Research Center in collaboration with a government/industry Digital Engineering Measures Working Group is creating the first formal measurement framework for this transformation. This article describes the research, formation of a causal measurement model, and initial specification of candidate measures.